DIGITAL LITERACY AS A MEANS OF PREVENTING CYBERCRIME (Heritage, 2022)
It is difficult today to imagine how a person would function in modern society without the use of Internet-based technologies. Everyday interactions that take place in the digital environment permeate all spheres of society, enabling communication, entertainment and business of users. However, the lack of technological skills and digital literacy in a large number of people increases the chances of them becoming victims of various types of cybercrime activities. Such activities can often have very severe physical, material and emotional consequences for Internet and social networks users. Also, it is not uncommon for the victim's interaction with a malicious cybercriminal to lead to tragic consequences. This problem especially affects the youngest population, who spend time every day in a virtual environment, often without the necessary technological skills and experience, but also without parental supervision. The fact that the number of young users of digital technologies is increasing every day on the world level should alert experts in this field, but also the governments of all countries to take this phenomenon more seriously. Digital literacy is emerging as an indisputable starting point that can be the most effective means of combating such malicious cyber activities.
Keywords: Internet, Social Networks, Digital Literacy, Cybercrime, Virtual Environment